Nasal specific IgE to Der p is not an acceptable screening test to predict the outcome of the nasal challenge test in patients with non-allergic rhinitis (2020)
Objectives: Nasal specific IgE (NsIgE) is the most common marker to identify type-2 inflammation in local allergic rhinitis (LAR). However, the comparison of NsIgE in different types of rhinitis, its frequency in tropical countries, and its diagnostic performance for predicting the outcome of a nasal challenge test (NCT) has had limited study. The main objective of this study was to explore the diagnostic performance of NsIgE to Dermatophagoides pteronyssinus (Der p) among different types of rhinitis and control subjects in a tropical population. Methods: We evaluated the frequency of NsIgE, systemic atopy (serum sIgE and Skin Prick Test), and nasal eosinophils, and we performed nasal challenge tests (NCTs) with Der p in 3 groups of patients; rhinitis without atopy (RWoA) (n = 25), rhinitis with atopy (RWA) (n = 25), and control subjects (n = 18). Results: NsIgE had a low sensitivity and specificity to predict a positive NCT in the RWoA group: 48% had NsIgE, but only 28% had a positive NCT. Among the RWA group 84% had NsIgE and 80% had a positive NCT; the association of NsIgE and positive NCT was high (>80%). In the control group 27.8% had NsIgE, but none had a positive NCT. Conclusions: NsIgE performs poorly in predicting NCT results in patients with non-allergic rhinitis. More methodical investigations are needed in this complex area of rhinitis. In patients with allergic rhinitis, NsIgE was useful in predicting a positive nasal challenge, but not superior to the systemic atopic test.